Improving Speaking English Ability Students With The Jigsaw Method At Second Semester Of PJKR STOK Bina Guna Medan - Elisa Haddina (Marga: Journal Of Innovation and Creatifity, 2025)
The aim of this research is to improve English Speaking through the Jigsaw method in second semester students at Sekolah Tinggi Olah Raga dan Kesehatan bina Guna Medan.. This class action research was carried out in the second semester of the 2023/2024 . The research consisted of two cycles with each cycle having three meetings. This research was conducted during a learning session to speak in dialogueWhen researchers conducted initial research, most of the students experience problems in communicating use English. Based on students' fear of making mistakes, lack of self-confidence,and has a low vocabulary. The researcher will sure by using the Jigsaw Method and the Students will more active in English Speaking , so that the will achieve the goal of English Speaking correctly because with more practice their vocabularies will increase and their skill English Speaking will be better. The researcher interest Researchers are interested in conducting research using the Jigsaw method because students are not confident and lack vocabulary in speaking English and hope that they can improve their speaking skills. The formulation of the problem is"How to improve your English speaking skills through Jigsaw Method at Second Semeter Students Sekolah Tinggi Olah Raga Kesehatan Bina Guna Medan In this study, The results of student responses show that most students are quite interested in applying the jigsaw method. there was an increase in the average score of students' speaking ability from 80.15, in the first cycle to 82.59 in the second cycle, accompanied by a boost in self-confidence.